Enhanced sensitivity to echo cues in blind subjects - Dufour, André; Després, Olivier; Candas, Victor (Experimental brain research, 2005)
Many studies have reported that blind people compensate for their visual deficit by sharpening auditory processes. Here we compare the sensitivity to echo cues between blind and sighted subjects. In the first experiment, the blind subjects were more accurate than the sighted subjects in localizing an object on the basis of echo cues. To ensure that enhanced echolocalization abilities were not only due to the fact that blind individuals are more used to consciously paying attention to echo cues and are more familiar with this kind of tasks than sighted subjects, we tested both groups of subjects in a simple azimuthal localization task of auditory stimuli. In this second experiment, we evaluated the influence of irrelevant echo signals on auditory localization by placing the subjects and the sound sources at different positions in a sound reverberant room. Results revealed that blind subjects exhibit a higher sensitivity to echo signals than sighted subjects.